The impact of semantic fields in realizing the meaning inside the informational message. - akkouchi, houda (Journal of Social Sciences and Humanities, 2021)
This study aims to explore the nature of meanings and the implications derived from the semantic fields theory, which showed the influence of it in producing the meaning of discourse within the informational message, as this theory arose in the arms of linguistics and its inspiration after that in the study of media speech as one of the types of discourses, especially related to the substance of the informational message within its social and cultural context, revealing the nature of the meaning and how meanings and indications are generated within the fundamental issues that the informational message provokes. What is the aspect of the effect that semantic fields have on producing meaning and generating connotations within the informational message? The significance of semantic fields within the media informational is shown in the compilation and classification of vocabulary indicating the essence of the speech in it, and the displacement of ambiguity when using these vocabulary, as well as generating meanings and indications to be directed towards the recipient, and providing a glossary of accurate words to demonstrate and produce meanings, which plays the primary role in the performance of the message The informational message performed best in a humble way between the sender and the recipient, as the two sides of the informational message.